2020
DOI: 10.1109/access.2020.2995716
|View full text |Cite
|
Sign up to set email alerts
|

A Hierarchical Teaching-Learning-Based Optimization Algorithm for Optimal Design of Hybrid Active Power Filter

Abstract: Hybrid active power filter (HAPF) has been widely used to suppress harmonics in the electric power system. However, selecting HAPF parameters accurately remains a primary challenge faced by researchers. To optimize HAPF parameters and reduce the harmonic pollution, this paper proposes an improved teaching-learning-based optimization algorithm, namely HTLBO. In HTLBO, a self-study strategy based on Lévy-Flight is developed to avoid the population falling into local optima. Furthermore, in the teaching phase, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Analog filter design was performed in reference [2]; this paper investigated the efficacy of metaheuristics for designing the analog filter circuit. A promising study with the Hierarchical Teaching Learning Based Optimization was conducted in reference [3]. Biswas et al in [4] applied Differential Evolution and its advanced version L-SHADE.…”
Section: Application Of Optimization Algorithms For Designing Filtersmentioning
confidence: 99%
“…Analog filter design was performed in reference [2]; this paper investigated the efficacy of metaheuristics for designing the analog filter circuit. A promising study with the Hierarchical Teaching Learning Based Optimization was conducted in reference [3]. Biswas et al in [4] applied Differential Evolution and its advanced version L-SHADE.…”
Section: Application Of Optimization Algorithms For Designing Filtersmentioning
confidence: 99%
“…Some students feel easy, while others feel it difficult. Therefore, it is very necessary to arrange assignment in different levels [8][9] . The term project content is designed in layers for students with different learning abilities, so that students at different levels can choose the assignment content suitable for their own difficulty.…”
Section: The Difference Of Content Depth Is Beneficial To Improve The...mentioning
confidence: 99%
“…Consequently, Biswas et al [15] proposed an algorithm based on differential evolution (DE) to optimize the parameters of HAPF design. In the reference [16], total voltage harmonic distortion and current harmonic distortion have been incorporated in a composite objective function with the aim to minimize total harmonic pollution. From the literature, it is concluded that the filter design problem is a complex problem.…”
Section: Introductionmentioning
confidence: 99%